Review: Franz X. Eder (Ed.) (2006). Historische Diskursanalysen. Genealogie, Theorie, Anwendungen [Historical Discourse Analysis. Genealogy, Theory, Applications] - Bretschneider, Falk (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2007)
Even if discourse analysis has now become a largely accepted analytic tool for historians, it still raises a number of problematic issues. The present volume aims at contributing to some of the most pressing theoretical and practical debates by giving tentative answers based on theoretical and empirical inquiry. It should be noted that, unlike in other publications, most authors in this collection have tried to analyze agents' specific relations to discourses. Thus the volume questions the widely assumed and disseminated dichotomy between text-based and action-based conceptions of discourse analysis by demonstrating that discourses are never impersonal structures. By giving concrete methodological orientations, this edited volume is an important contribution to historical discourse analysis.URN: urn:nbn:de:0114-fqs0702179